One Juliet and four Romeos: VeA and its methyltransferases - Sarikaya-Bayram, Özlem; Palmer, Jonathan M.; Keller, Nancy; Braus, Gerhard H.; Bayram, Özgür (Frontiers in Microbiology, 2015)
Fungal secondary metabolism has become an important research topic with great biomedical and biotechnological value. In the postgenomic era, understanding the diversity and the molecular control of secondary metabolites are two challenging tasks addressed by the research community. Discovery of the LaeA methyltransferase 10 years ago opened up a new horizon on the control of secondary metabolite research when it was found that expression of many secondary metabolite gene clusters is controlled by LaeA. While the molecular function of LaeA remains an enigma, discovery of the velvet family proteins as interaction partners further extended the role of the LaeA beyond secondary metabolism. The heterotrimeric VelB-VeA-LaeA complex plays important roles in development, sporulation, secondary metabolism and pathogenicity. Recently, three other methyltransferases have been found to associate with the velvet complex, the LaeA-like methyltransferase F (LlmF) and the methyltransferase heterodimers VipC-VapB. Interaction of VeA with at least four methyltransferase proteins indicates a molecular hub function for VeA that questions: Is there a VeA supercomplex or is VeA part of a highly dynamic cellular control network with many different partners?